John, Qumran, and the Dead Sea scrolls: sixty years of discovery and debate - Coloe, Mary L.; Thatcher, Tom (Society of Biblical Literature : early Judaism and its literature, 2011)
Preface. New light on John and Qumran / Mary Coloe and Tom Thatcher -- The past decade of Qumran studies : 1997/2007 / Eileen Schuller -- John and Qumran : discovery and interpretation over sixty years / Paul N. Anderson -- "Mystery" in the Dead Sea scrolls and the fourth gospel / John Ashton -- Luke, John, and the Dead Sea scrolls / George J. Brooke -- John, Qumran, and virtuoso religion / Brian J. Capper -- Purification in the fourth gospel in light of Qumran / Hannah K Harrington -- "Protect them from the evil one" (John 17:15) : light from the Dead Sea scrolls / Loren T. Stuckenbruck -- The fourth evangelist and the Dead Sea scrolls : assessing trends over nearly sixty years / James H. Charlesworth